Romania : Seventh Review Under the Stand-By Arrangement Cancellation of Current Stand-By Arrangement and Request for a New Stand-By Arrangement-Staff Report; Supplement on the Assessment of the Risks to the Fund and the Fund's Liquidity Position; Supplementary Information; Press Release on the Executive Board Discussion; Statement by the Executive Director and the Senior Advisor to the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2011)
Romania's external position continues to improve. Inflation peaked in December 2010, and is now likely to decline. Financial market stress has remained relatively low in recent months. The current account deficit improved from 13 1/2 percent of GDP in 2007 to about 4 1/4 percent of GDP in 2010, driven by a strong shrinking trade deficit. Significant progress has been made under the Stand-By Arrangement (SBA) in achieving fiscal consolidation and safeguarding the financial sector. Most performance criteria and structural benchmarks were met throughout the program.